2021
DOI: 10.1002/ctm2.552
|View full text |Cite
|
Sign up to set email alerts
|

Lipid raft‐disrupting miltefosine preferentially induces the death of colorectal cancer stem‐like cells

Abstract: BackgroundLipid rafts (LRs), cholesterol‐enriched microdomains on cell membranes, are increasingly viewed as signalling platforms governing critical facets of cancer progression. The phenotype of cancer stem‐like cells (CSCs) presents significant hurdles for successful cancer treatment, and the expression of several CSC markers is associated with LR integrity. However, LR implications in CSCs remain unclear.MethodsThis study evaluated the biological and molecular functions of LRs in colorectal cancer (CRC) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Five studies associated with patient-derived RC organoid application were finally considered. All publications or clinical studies that met the criteria were included in Table 2, and some of the publications and clinical studies excluded are shown in Table 1 (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). They are presented subsequently in this order, reflecting the scientific continuum, moving from the characterization and acquisition of knowledge to the interpretation and finally toward clinical implementation.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies associated with patient-derived RC organoid application were finally considered. All publications or clinical studies that met the criteria were included in Table 2, and some of the publications and clinical studies excluded are shown in Table 1 (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). They are presented subsequently in this order, reflecting the scientific continuum, moving from the characterization and acquisition of knowledge to the interpretation and finally toward clinical implementation.…”
Section: Resultsmentioning
confidence: 99%
“…Priming of the inflammasome pathway by LPS is dependent on TLR receptors, which are enriched in membrane lipid rafts. Miltefosine-mediated disruption of lipid rafts can attenuate TLR signaling pathway 10,50 , thus we tested the effects of Miltefosine on direct NLRP3 inflammasome activity in live animals. We chose the peritoneal cavity as the site for NLRP3 inflammasome activity as it contains the liver, spleen, GI tract, and a variety of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells are previously confirmed to have higher levels of lipid rafts than normal cells [ 11 , 12 ], while emerging evidence indicates that CSCs contain more lipid rafts than cancer cells. That is, the relative amount of lipid rafts: CSCs > cancer cells > normal cells [ 13 ]. Specifically, a study using filipin and conjugated cholera toxin B (CtxB) for plasma membrane cholesterol and GM1 staining showed that the cancer cell lines (PC-3, LNCaP, MCF-7, and MDA-MB-231) have stronger staining than the normal cell lines (PZ-HPV7 and MCF-10A), suggesting higher levels of rafts/ caveolae in the cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the lipid rafts of CSCs, the data from CtxB immunostaining and flow cytometry assay have shown that the levels of lipid rafts in CD44 high colorectal cancer cells are higher, as the median fluorescence intensity ratio of lipid rafts within CD44 high cells is 10%-30% stronger than CD44 low cells. Importantly, CtxB high cells showed a greater sphere‐forming capacity [ 13 ]. In addition, CD133 + pancreatic cancer cells have more caveolin-1and cholesterol than CD133 − cells by Western blotting, real-time PCR and Amplex red cholesterol assay, indicating higher levels of lipid rafts in CD133 + CSCs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation